Elastomeric composite particles, method for producing the same, and method for producing elastomeric spherical particles

JP2025027238APending Publication Date: 2025-02-27SHIN ETSU CHEMICAL CO LTD +1
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
JP2023131875
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-14
Publication Date
2025-02-27

AI Technical Summary

Benefits of technology

【0018】 本発明のエラストマー複合粒子は、粒子中に分解性を有する単位骨格のポリエステル構造を有しており、水分存在下において粒子の架橋構造が切断されるため、分解性を有する。特に、粒子中のポリエステル構造として、微生物認識骨格であるポリ-ε-カプロラクトン構造を有する粒子は、エラストマー球状粒子やエラストマー複合粒子の環境分解性、生分解性が期待できる。 従って、本発明のエラストマー複合粒子は、(生)分解性を有する粒子であり、環境負荷低減材料としての利用が期待できる。 また、本発明のエラストマー複合粒子は、凝集性が低く分散性の高い粒子であるため、各種樹脂配合時の応力緩和効果が高まることが期待される。さらに化粧品用途においては、本発明のエラストマー複合粒子を配合することで、柔らかな感触、なめらかさ等の使用感、及び伸展性の付与効果が高くなることが期待される。 本発明のエラストマー複合粒子は表面に付着させるシリカ微粒子の被覆(付着)量の調整により親水性粒子とすることも可能であり、水性の化粧料に乳化剤等の分散剤を使用することなく配合することが可能になる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025027238000001_ABST
    Figure 2025027238000001_ABST
Patent Text Reader

Abstract

To provide: elastomeric composite particles containing elastomeric spherical particles having, as a constituent unit, a (co)polymer that is highly degradable when exposed to an external stimulus such as light; and methods for producing elastomeric spherical particles and elastomeric composite particles.SOLUTION: The present invention provides elastomeric composite particles having polyorganosilsesquioxane or silica on the surface of elastomeric spherical particles which have a volume average particle diameter of 0.5-200 μm and which are crosslinked particles of a copolymer having a polyester structure and a polyether structure.SELECTED DRAWING: Figure 3
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an elastomer composite particle and a method for producing the same, and a method for producing an elastomer spherical particle. [Background technology]

[0002] Conventionally, the raw rubber used in rubber products is [1] Polymers whose repeating units consist only of conjugated diene units, such as butadiene rubber, isoprene rubber, chloroprene rubber, and natural rubber. [2] Polymers whose repeating units essentially consist of conjugated diene units and aromatic vinyl units, such as styrene-butadiene copolymer rubber, styrene-isoprene copolymer rubber, and styrene-isoprene-butadiene copolymer rubber. [3] Polymers whose repeating units essentially consist of conjugated diene units and α,β-unsaturated nitrile units, such as acrylonitrile-butadiene copolymer rubber. [4] Polymers whose repeating units are essentially acrylate units, such as acrylic rubber. [5] A polymer having a repeating unit of ethylene, an α-olefin having 3 to 12 carbon atoms, and optionally a non-conjugated polyene, such as ethylene-propylene rubber. [6] Polymers whose repeating units consist of dimethylsiloxane units, such as silicone rubber. These are some of the most commonly used.

[0003] These elastomer (rubber) spherical particles obtained from raw rubber, especially those with an organic skeleton, are used primarily as electronic materials, including for electronic devices, to improve various properties such as impact resistance, thermal shock resistance, and adhesion.

[0004] On the other hand, silicone rubber spherical particles and powders have been proposed for use in a wide range of industrial fields. For example, it has been suggested that it be added to synthetic resin materials (Patent Documents 1 and 2), synthetic rubber materials (Patent Document 3), cosmetics (Patent Documents 4 to 7), and the like.

[0005] Silicone rubber spherical particles are used as a stress reducing agent for organic resins such as epoxy resin, taking advantage of their "flexibility." In other words, the difference in thermal expansion coefficient between electronic components and organic resins such as epoxy resin can cause stress to be applied to the resin, which can lead to cracks and breakage, but adding silicone rubber spherical particles can prevent this.

[0006] Specifically, proposed epoxy resins include those containing spherical particles of a cured polymer containing linear organopolysiloxane blocks (Patent Document 8) and those containing spherical particles in which the surface of spherical silicone rubber particles is coated with polyorganosilsesquioxane (Patent Document 9).

[0007] Also disclosed is a method for preparing silicone-containing rubber spherical particles by copolymerizing, in an emulsion system, a (meth)acrylic acid ester and a diorganopolysiloxane having an organic group containing a radically polymerizable functional group at one end (Patent Document 10). The organic rubber spherical particles are used for the purpose of imparting lubricity to thermoplastic resins.

[0008] Furthermore, organic crosslinked rubber spherical particles (Patent Document 11) obtained by crosslinking a liquid composition consisting of an organic compound having an aliphatic unsaturated bond and a silicon-containing organic compound having silicon-bonded hydrogen atoms through a hydrosilylation reaction have been proposed as having excellent dispersibility in various resins, paints, rubbers, and other components and excellent handling and workability.

[0009] Furthermore, silicone rubber spherical particles are used in a wide range of cosmetics and cosmetic materials, such as makeup cosmetics such as foundations and makeup bases, basic cosmetics such as creams and milky lotions, and sunscreen cosmetics, for the purposes of imparting a soft feel and smoothness to cosmetics, scattering light to create a natural finish, and making pores and wrinkles less visible.

[0010] For example, proposed cosmetics include polymethylsilsesquioxane particles / powder (Patent Document 12), makeup cosmetics including spherical silicone rubber particles / powder (Patent Document 13), and cosmetics including silicone composite particles / powder in which silicone rubber spherical particles are coated with polyorganosilsesquioxane resin (Patent Document 14). As described above, these silicone rubber spherical particles and composite particles in which silicone rubber spherical particles are coated with polyorganosilsesquioxane resin can impart a feeling of use such as a soft feel and smoothness to cosmetics. [Prior art documents] [Patent documents]

[0011] [Patent Document 1] Special Publication No. 63-12489 [Patent Document 2] Special Publication No. 6-55805 [Patent Document 3] Japanese Patent Application Publication No. 2-102263 [Patent Document 4] Japanese Patent Application Publication No. 8-12546 [Patent Document 5] Japanese Patent Application Publication No. 8-12545 [Patent Document 6] Special Publication No. 4-17162 [Patent Document 7] Special Publication No. 4-66446 [Patent Document 8] Japanese Patent Application Publication No. 58-219218 [Patent Document 9] Japanese Patent Application Publication No. 8-85753 [Patent Document 10] Japanese Patent Application Publication No. 10-182987 [Patent Document 11] JP 2001-40214 A [Patent Document 12] Japanese Patent Application Publication No. 63-297313 [Patent Document 13] Japanese Patent Application Publication No. 8-12524 [Patent Document 14] Japanese Patent Application Publication No. 9-20631 Summary of the Invention [Problem to be solved by the invention]

[0012] However, when these silicone rubber spherical particles, which are blended into various resins and cosmetics, etc., are released or run off into the natural environment, such as soil, land water, seawater, or ocean, they are predicted to remain in the environment without being decomposed because they do not have a skeleton or unit that has or provides degradability within the particle structure.In addition, because these particles have a small particle size, it is very difficult to recover them, and it is currently unavoidable that they will run off into the ocean, etc.

[0013] In addition, plastics that have flowed into the ocean, and microplastics that have been broken down and miniaturized to millimeter to micrometer sizes, have the ability to adsorb harmful substances and pathogens present in the environment. There are concerns that if marine organisms accidentally ingest these, they could have a negative impact on the ecosystem, and so there are beginning to be moves to regulate microplastics.

[0014] In light of this, there is a growing demand for silicone or elastomer spherical particles that decompose in the environment after use and do not remain as particles (solid matter).In order for these elastomer spherical particles to decompose in the environment, the cross-linked structure that forms the particles needs to be cut and decomposed in the environment, but silicone rubber spherical particles are not degradable due to their structure.

[0015] The present invention has been made in consideration of the above circumstances, and an object of the present invention is to provide elastomer composite particles containing elastomer spherical particles having as structural units (co)polymers that are highly degradable in natural environments including soil, land water, and ocean / seawater due to external stimuli such as light, heat, acid / base, and the action of microorganisms, fungi, etc. Another object of the present invention is to provide a method for producing elastomer spherical particles and elastomer composite particles having a highly degradable (co)polymer as a constituent unit. [Means for solving the problem]

[0016] As a result of intensive research into achieving the above-mentioned object, the inventors have discovered that elastomer composite particles having as their core particles elastomer spherical particles, which are crosslinked particles of a copolymer having a specific polyester structure and a polyether structure, can solve the above-mentioned problems, and have thus completed the present invention.

[0017] Therefore, the present invention provides the following elastomer composite particles, a method for producing elastomer spherical particles, and a method for producing elastomer composite particles. [1]. The elastomer composite particles have a volume average particle size of 0.5 to 200 μm, and are comprised of elastomer spherical particles which are crosslinked particles of a copolymer having a polyester structure and a polyether structure, and which have polyorganosilsesquioxane or silica on the surface thereof. [2]. The elastomer composite particle according to [1], wherein the copolymer is a polyester-polyether copolymer having at least two radically polymerizable unsaturated groups in one molecule. [3]. The elastomer composite particle according to [2], wherein the copolymer is a polyester-polyether copolymer represented by the following general formula (1) or (2): [ka] (In general formula (1), R 1 each independently represents a divalent hydrocarbon group having 1 to 10 carbon atoms; R 2 each independently represents a radically polymerizable functional group-containing organic group represented by the following general formula (3a), (3b), or (3c), each k is independently a number that is 1≦k≦10, each l is a number that is 1≦l≦1,000, each m is a number that is 1≦m≦1,000, and each n is independently a number that is 1≦n≦100. In general formula (2), R 3 each independently represents a divalent hydrocarbon group having 1 to 10 carbon atoms; R 4each independently represents a radically polymerizable functional group-containing organic group represented by the following general formula (4a) or (4b), each p is independently a number of 1≦p≦10, each l is a number of 1≦l≦1,000, each m is a number of 1≦m≦1,000, and each q is independently a number of 1≦q≦100. [ka] (In general formulas (3a), (3b), (3c), (4a) and (4b), R 5 each independently represents a divalent hydrocarbon group having 1 to 8 carbon atoms; R 6 each independently represents a hydrogen atom or a hydrocarbon group having 1 to 3 carbon atoms. [4]. The elastomer composite particle according to [2], wherein the copolymer is a polyester-polyether copolymer represented by the following general formula (5): [ka] (In general formula (5), R 1 each independently represents a divalent hydrocarbon group having 1 to 10 carbon atoms; R 2 each independently represents a radically polymerizable functional group-containing organic group represented by the following general formula (3a), (3b) or (3c), l is a number that satisfies 1≦l≦1,000, m is a number that satisfies 1≦m≦1,000, and each r is independently a number that satisfies 1≦r≦100. [ka] (In general formulas (3a), (3b) and (3c), R 5 each independently represents a divalent hydrocarbon group having 1 to 8 carbon atoms; R 6 each independently represents a hydrogen atom or a hydrocarbon group having 1 to 3 carbon atoms. [5]. A method for producing elastomer spherical particles, comprising the following steps i) to iii): i) A step of preparing a suspension composition by stirring and suspending the following components (A), (B), (C), and (D): (A) A copolymer having a polymerizable group and having a polyester structure and a polyether structure (B) an aqueous phase component or an oil phase component in which the component (A) is insoluble or poorly soluble (C) Suspension (D) Polymerization initiator ii) A step of obtaining a dispersion of elastomer spherical particles by radically polymerizing the component (A) in the suspension composition obtained in the step i). iii) A process for obtaining elastomeric spherical particles by washing and drying to remove the continuous phase (B) from the dispersion of elastomeric spherical particles obtained in the process ii). [6]. A method for producing elastomer composite particles according to any one of [1] to [4], comprising the following step iv): iv) A step of adding the following component (I) to a liquid phase containing the following components (E), (F), (G), and (H) and subjecting the component (I) to a hydrolysis / polymerization reaction. (E) Elastomer spherical particles having a volume average particle size of 0.5 to 200 μm, which are crosslinked particles containing structural units derived from a copolymer having a polyester structure and a polyether structure, produced by the method according to [5]. (F) Alkaline substances (G) One or more selected from cationic surfactants and cationic water-soluble polymer compounds (H)Water (I) Trialkoxysilane or tetraalkoxysilane Effect of the Invention

[0018] The elastomer composite particles of the present invention have a polyester structure as a degradable unit skeleton in the particles, and the crosslinked structure of the particles is broken in the presence of moisture, so that the particles are degradable. In particular, particles having a poly-ε-caprolactone structure, which is a microorganism recognition skeleton, as the polyester structure in the particles can be expected to have environmental degradability and biodegradability as elastomer spherical particles and elastomer composite particles. Therefore, the elastomer composite particles of the present invention are particles having (biodegradability), and are expected to be used as materials that reduce the environmental load. In addition, since the elastomer composite particles of the present invention are particles with low coagulation and high dispersibility, it is expected that the stress relaxation effect will be improved when various resins are blended. Furthermore, in cosmetic applications, it is expected that blending the elastomer composite particles of the present invention will improve the feel of use, such as softness and smoothness, and the effect of imparting extensibility. The elastomer composite particles of the present invention can also be made into hydrophilic particles by adjusting the coating (attachment) amount of silica fine particles attached to the surface, making it possible to incorporate them into aqueous cosmetics without using a dispersing agent such as an emulsifier. [Brief description of the drawings]

[0019] [Figure 1] 1 is an electron microscope photograph of the elastomer spherical particles obtained in Production Example 1. [Diagram 2] 1 is an electron microscope photograph of the elastomer spherical particles obtained in Production Example 3. [Diagram 3] 1 is an electron microscope photograph (magnification x1,000) of the elastomer composite particles (silica-coated elastomer spherical particles) obtained in Example 3. [Figure 4] 1 is an electron microscope photograph (magnification: ×7,500) of the elastomer composite particles (silica-coated elastomer spherical particles) obtained in Example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] The present invention will be described in detail below.

[0021] [Elastomer composite particles] The elastomer composite particles of the present invention have polyorganosilsesquioxane or silica on the surface of elastomer spherical particles, which are crosslinked particles of a copolymer having a polyester structure and a polyether structure, and preferably have spherical fine particles of polyorganosilsesquioxane or spherical fine particles of silica adhered to the particle surface of the elastomer spherical particles.

[0022] The elastomer composite particles of the present invention preferably have a spherical shape. In the present invention, the term "spherical" does not only refer to a particle shape that is a perfect sphere, but also includes a deformed ellipsoid having an aspect ratio (length of the longest axis / length of the shortest axis) that is usually in the range of 1 to 4, preferably 1 to 2, more preferably 1.0 to 1.6, and even more preferably 1.0 to 1.4 on average. As shown in the production method described later, in the case of a method in which a copolymer having a polyester structure and a polyether structure is suspended and dispersed using a suspending agent and crosslinked, the shape of the obtained particles is spherical. The shape of the elastomer composite particles can be confirmed by observation using, for example, an optical microscope or an electron microscope, and the aspect ratio is a value calculated by measuring the length of the longest axis and the shortest axis of 50 particles selected from a micrograph and averaging the results.

[0023] In the present invention, the volume average particle diameter of the elastomer composite particles is in the range of 0.5 to 200 μm, more preferably in the range of 1.0 to 50 μm. If the volume average particle diameter is larger than the upper limit, the particles may have a reduced silky feel, a rough feel, and a reduced light diffusibility. If the volume average particle diameter is smaller than the lower limit, the particles have a reduced fluidity and a high degree of cohesion, which is undesirable because it is not possible to impart sufficient smoothness and light diffusibility. The volume average particle diameter of the elastomer composite particles of the present invention indicates a value measured as follows. Prior to measuring the volume average particle diameter, the particle diameters of 50 particles are randomly selected from a micrograph of the elastomer composite particles, and the average value is judged to be equal to or greater than 1 μm or less. A dispersion liquid is prepared by redispersing the elastomer composite particles in water using various surfactants, and if the judgment result is equal to or greater than 1 μm, the volume average particle diameter is indicated as a value measured by an electrical resistance method, and if the judgment result is less than 1 μm, the volume average particle diameter is indicated as a value measured by a laser diffraction / scattering method.

[0024] It is preferable that the rubber (elastomer) which is a component of the elastomer composite particles does not have tack or stickiness. The rubber hardness of the rubber (elastomer) which is a component of the elastomer composite particles is preferably in the range of 5 to 90, more preferably in the range of 10 to 80, when measured by a type A durometer specified in JIS K6253. In addition, the rubber hardness of the rubber (elastomer) which is a component of the elastomer composite particles is preferably in the range of 5 to 90, more preferably in the range of 20 to 85, and even more preferably in the range of 40 to 85, when measured by an Asker rubber hardness tester type C specified in the Society of Rubber Industry Standards (SRIS). If the rubber hardness value measured is less than 5, the particles may become more cohesive and dispersible. If the rubber hardness value is more than 90, the soft feel may decrease, which is not preferable.

[0025] - Elastomer spherical particles, which are crosslinked particles of copolymers having polyester and polyether structures The elastomer spherical particles in the elastomer composite particles of the present invention are further preferably particles made of a polyester-polyether copolymer having at least two radically polymerizable unsaturated groups in one molecule, i.e., crosslinked particles of a polyester-polyether copolymer having at least two radically polymerizable unsaturated groups in one molecule. The aspect ratio of the elastomer spherical particles in the elastomer composite particles of the present invention is defined in the same manner as above, and the aspect ratio (length of longest axis / length of shortest axis) of the elastomer spherical particles is usually in the range of 1 to 4, preferably 1 to 2, more preferably 1.0 to 1.6, and even more preferably 1.0 to 1.4, on average. The volume average particle size of the elastomer spherical particles in the elastomer composite particles of the present invention is also defined in the same manner as above, and the volume average particle size of the elastomer spherical particles is in the range of 0.5 to 200 μm, more preferably in the range of 1.0 to 50 μm.

[0026] The polyester-polyether copolymer having at least two radically polymerizable unsaturated groups in one molecule is preferably a copolymer represented by the following general formula (1) or (2). [ka] (In general formula (1), R 1 each independently represents a divalent hydrocarbon group having 1 to 10 carbon atoms; R 2 each independently represents a radically polymerizable functional group-containing organic group represented by the following general formula (3a), (3b), or (3c), each k is independently a number that is 1≦k≦10, each l is a number that is 1≦l≦1,000, each m is a number that is 1≦m≦1,000, and each n is independently a number that is 1≦n≦100. In general formula (2), R 3 each independently represents a divalent hydrocarbon group having 1 to 10 carbon atoms; R 4 each independently represents a radically polymerizable functional group-containing organic group represented by the following general formula (4a) or (4b), each p is independently a number of 1≦p≦10, each l is a number of 1≦l≦1,000, each m is a number of 1≦m≦1,000, and each q is independently a number of 1≦q≦100. [ka] (In general formulas (3a), (3b), (3c), (4a) and (4b), R 5 each independently represents a divalent hydrocarbon group having 1 to 8 carbon atoms; R 6 each independently represents a hydrogen atom or a hydrocarbon group having 1 to 3 carbon atoms.

[0027] R 1 Examples of alkylene groups include methylene, ethylene, propylene, trimethylene, tetramethylene, pentamethylene, hexamethylene, heptamethylene and octamethylene groups, and preferably methylene, ethylene, trimethylene and tetramethylene groups.

[0028] R 3Examples of alkylene groups include methylene, ethylene, propylene, trimethylene, tetramethylene, pentamethylene, hexamethylene, heptamethylene and octamethylene groups, and preferably methylene, ethylene, trimethylene and tetramethylene groups.

[0029] R 2 represents a radical polymerizable functional group-containing organic group represented by general formula (3a), (3b), or (3c), and R 4 represents an organic group containing a radical polymerizable functional group represented by general formula (4a) or (4b). In general formulas (3b), (3c), (4a), and (4b), R 5 Examples of alkylene groups include methylene, ethylene, propylene, trimethylene, tetramethylene, pentamethylene, hexamethylene, heptamethylene and octamethylene groups, and preferably methylene, ethylene, trimethylene and tetramethylene groups. In general formulas (3a), (3b), (3c), (4a), and (4b), R 6 Examples of the alkyl group include a hydrogen atom, and an alkyl group having 1 to 3 carbon atoms, such as a methyl group, an ethyl group, or a propyl group, and preferably a hydrogen atom or a methyl group. The radically polymerizable functional group-containing organic groups represented by the general formulae (3a), (3b), (3c), (4a), and (4b) are residues derived from polymerizable monomers. Specific examples of the polymerizable monomers include hydroxyl group-containing (meth)acrylic acid esters, isocyanate group-containing (meth)acrylic acid esters, and (meth)acrylic acid chlorides.

[0030] Examples of hydroxyl group-containing (meth)acrylic acid esters include hydroxyalkyl esters of (meth)acrylic acid having 2 to 8 carbon atoms, such as hydroxyethyl (meth)acrylic acid ester and hydroxypropyl (meth)acrylic acid ester, and carboxy (meth)acrylates, such as carboxyethyl (meth)acrylate, (meth)acryloyloxyethyl succinate, and (meth)acryloyloxyethyl phthalate. Examples of the isocyanate group-containing (meth)acrylic ester include isocyanate ethyl (meth)acrylic ester, isocyanate propyl (meth)acrylic ester, isocyanate butyl (meth)acrylic ester, and isocyanate hexyl (meth)acrylic ester. Examples of the (meth)acrylic acid chloride include acryloyl chloride, methacryloyl chloride, acryloyl bromide, and methacryloyl bromide.

[0031] The polyester structure (unit) of the polyester-polyether copolymer having at least two radically polymerizable unsaturated groups in one molecule is preferably an aliphatic polyester which has or is considered to have high decomposition ability. Examples of aliphatic polyesters include poly-ε-caprolactone, poly-β-propiolactone, γ-butyrolactone, polylactic acid, polyhydroxybutyrate, polyglycolic acid, polyethylene adipate, polyhydroxybutyric acid, polyethylene succinate, and polybutylene succinate. From the viewpoints of degradability and ease of handling, those having a poly-ε-caprolactone structure are particularly preferred.

[0032] In the general formula (1), each k is independently a number satisfying 1≦k≦10, and preferably a number satisfying 1≦k≦6. In the general formula (2), each p is independently a number satisfying 1≦p≦10, and preferably a number satisfying 1≦p≦6.

[0033] In the general formula (1), each n is independently a number satisfying 1≦n≦100, preferably a number satisfying 1≦n≦50, and more preferably a number satisfying 2≦n≦20. In the general formula (2), each q is independently a number satisfying 1≦q≦100, preferably a number satisfying 1≦q≦50, and more preferably a number satisfying 2≦q≦20. When the values ​​of n and q are larger than the upper limit values, the crystallinity increases due to intramolecular / intermolecular interactions of the polymer caused by the ester structure (units), and if the fluidity of the copolymer is too low, this may affect the handleability in the preparation process of the suspension composition described below.

[0034] In the general formulas (1) and (2), l is a number satisfying 1≦l≦1,000, and preferably 2≦l≦100. In the general formulas (1) and (2), m is a number satisfying 1≦m≦1,000, and preferably 10≦m≦500. If the value of l is greater than the upper limit, the crystallinity increases due to the intramolecular / intermolecular interactions of the polymer due to the ethylene oxide structure (unit), and the fluidity of the copolymer may decrease. In this case, as in the above, the handleability may be adversely affected in the preparation step of the suspension composition described below, which is undesirable.

[0035] As the polyester-polyether copolymer having at least two radically polymerizable unsaturated groups in one molecule, from the viewpoints of ease of handling of raw materials and ease of production, a copolymer represented by the following general formula (5) or (6) is more preferable. [ka] (In general formula (5), R 1 each independently represents a divalent hydrocarbon group having 1 to 10 carbon atoms; R 2 each independently represents a radically polymerizable functional group-containing organic group represented by general formula (3a), (3b) or (3c), l is a number of 1≦l≦1,000, m is a number of 1≦m≦1,000, and each r is independently a number of 1≦r≦100. (In general formula (6), R 3 each independently represents a divalent hydrocarbon group having 1 to 10 carbon atoms; R 4 each independently represents a radically polymerizable functional group-containing organic group represented by general formula (4a) or (4b), l is a number of 1≦l≦1,000, m is a number of 1≦m≦1,000, and each s is independently a number of 1≦s≦100.

[0036] Method for producing polyester-polyether copolymer Examples of a method for producing the polyester-polyether copolymer constituting the elastomer composite particle of the present invention include a production method in which various polyethers containing active hydrogen, such as polyethers having a hydroxyl group, carboxy-modified polyethers, and amino-modified polyethers, are used as starting materials, and cyclic-ε-caprolactone, γ-butyrolactone, or the like is subjected to ring-opening polymerization to obtain poly-ε-caprolactone-modified polyethers and poly-γ-butyrolactone-modified polyethers, and then a polymerizable monomer having an unsaturated group capable of radical polymerization is introduced via an ester bond, an ether bond, a urethane bond, an amide bond, or the like. From the viewpoint of reactivity during production, the terminal structure of each polyether is preferably a structure in which a reactive functional group is bonded to a primary carbon atom.

[0037] In the above-mentioned production method, examples of reaction conditions include the following, but are not limited to these reaction conditions. A poly-ε-caprolactone-modified polyether is obtained by adding, for example, 3.0 to 4.0 equivalents (functional group equivalent ratio) of cyclic-ε-caprolactone to 1.0 equivalent of a polyether containing active hydrogen, such as a polyether or a carboxy-modified polyether, and reacting the mixture at 120°C for 4 to 6 hours in the presence of a conventionally known ring-opening polymerization catalyst. Next, to 1.0 mol of the hydroxyl group of the obtained poly-ε-caprolactone-modified polyether, for example, 1.0 to 1.25 mol (functional group equivalent ratio) of a (meth)acrylic acid chloride such as acrylic acid chloride or an isocyanate group-containing (meth)acrylic acid ester such as isocyanate ethyl (meth)acrylate is added, and a reaction catalyst is added as necessary, followed by reaction at 40 to 100°C for 4 hours or more. After the reaction, the crude product is quenched with alcohol or the like, and then the by-products are removed by filtration, washing with water, and / or adsorption treatment. Finally, the solvent is distilled off to obtain an acrylic-modified poly-ε-caprolactone polyether (polyester-polyether copolymer).

[0038] When a polyether having a hydroxyl group is used as a starting material, examples of the polyester-polyether copolymer include those shown in formulas (7a) and (7b) (only one side structure is shown because the structure is symmetrical). [ka]

[0039] In formulas (7a) and (7b), R 5 is a divalent hydrocarbon group having 1 to 8 carbon atoms, and R 6 is a hydrogen atom or a hydrocarbon group having 1 to 3 carbon atoms. l, m, and r are 1≦l≦1,000, 1≦m≦1,000, and 1≦r≦30, and preferably 2≦l≦100, 10≦m≦500, and 2≦r≦10.

[0040] When a carboxy-modified polyether is used as a starting material, examples of polyester-polyether copolymers include those shown in formulas (8a) and (8b) (only one end is shown due to the symmetrical structure). [ka]

[0041] In formulas (8a) and (8b), R 5 is a divalent hydrocarbon group having 1 to 8 carbon atoms, and R 6 is a hydrogen atom or a hydrocarbon group having 1 to 3 carbon atoms. Furthermore, l, m, s, and t are within the range of 1≦l≦1,000, 1≦m≦1,000, 1≦s≦30, and 0≦t≦10, and preferably 2≦l≦100, 10≦m≦500, 2≦s≦10, and 1≦t≦10.

[0042] The catalyst used in the ring-opening polymerization of cyclic-ε-caprolactone may be any of the conventionally known catalysts, and is not limited thereto. Specific examples include organic titanium compounds such as tetramethoxytitanium, tetraethoxytitanium, tetra-n-propoxytitanium, and tetra-n-butoxytitanium; organic tin compounds such as di-n-butyltin laurate, diisobutyltin oxide, and dibutyltin diacetate; acetates of magnesium, calcium, zinc, and the like; antimony oxide; stannous halides; and perchloric acid.

[0043] The amount of the ring-opening polymerization catalyst added may be in the range of 1 to 10,000 ppm, and preferably 10 to 1,000 ppm, based on the ε-caprolactone monomer (cyclic-ε-caprolactone).

[0044] As a method for introducing a polymerizable monomer having an unsaturated group capable of radical polymerization into the poly-ε-caprolactone-modified polyether, various catalysts may be used depending on the reaction substrate (reactive functional group) of the polymerizable monomer and the skeleton to be formed, and a conventionally known catalyst may be used.

[0045] Examples of (esterification) catalysts used in the esterification reaction when the reaction between the polymerizable monomer and the poly-ε-caprolactone-modified polyether is an esterification reaction include alcoholates, carboxylates, or chelate compounds of titanium, zirconium, tin, aluminum, and zinc, as well as Lewis acid catalysts such as boron trifluoride and boron trifluoride etherate; acid catalysts such as hydrochloric acid, sulfuric acid, hydrogen bromide, acetic acid, trifluoroacetic acid, methanesulfonic acid, and p-toluenesulfonic acid; and amine catalysts such as pentamethyldiethylenetriamine (PMDETA), trimethyltriazacyclononane (TACN), triethylamine (TEA), 4-(N,N-dimethylamino)pyridine (DMAP), 1,4-diazabicyclo(2,2,2)octane (DABCO), and tetramethylethylenediamine (TMEDA). Among these, amine catalysts are preferred from the standpoint of stability of the product obtained by the esterification reaction and from the economical standpoint.

[0046] In addition, when using an amine catalyst, a dehydration condensation agent may be added to improve the reaction efficiency. As the dehydration condensation agent, a conventionally known agent can be used, for example, 1,1'-carbonyldiimidazole (CDI), N,N'-dicyclohexylcarbodiimide (DCC), N,N'-diisopropylcarbodiimide (DIC), 1-ethyl-3-(3-dimethylaminopropyl)-carbodiimide (EDC), 1-ethyl-3-(3-dimethylaminopropyl)-carbodiimide hydrochloride (EDC·HCl), and 1-[bis(dimethylamino)methylene]-1H-1,2,3-triazolo[4,5-b]pyridinium 3-oxide hexafluorophosphate (HATU) and the like can be mentioned, but are not limited thereto.

[0047] Examples of catalysts used in the urethanization reaction in the case where the reaction between a polymerizable monomer and a poly-ε-caprolactone-modified polyether is a urethanization reaction include amines such as triethylamine, triethylenediamine, pentamethylenediethylenetriamine, N,N-dimethylethanolamine, 1,4-diazabicyclo(2,2,2)octane (DABCO), pyridine, and N,N,N',N'-tetramethyl-1,3-propanediamine (TMPDA); organic tin compounds such as di-n-butyltin laurate, diisobutyltin oxide, dibutyltin diacetate, dibutyltin dilaurate (DBTL), and dioctyltin dineodecanoate; tetramethoxytitanium, tetraethyltin, and the like. organic titanium compounds such as titanium oxy, tetra-n-propoxy, titanium tetrabutoxy, tetrakis(octyloxy)titanium, titanium acetylacetonate, titanium tetraacetylacetonate, dodecylbenzenesulfonic acid titanium compound, phosphate titanium complex, titanium triethanolamine, titanium diisopropoxybis(ethylacetoacetate); organic zirconium compounds such as n-propyl zirconate, n-butyl zirconate, zirconium tetraacetylacetonate, zirconium dibutoxybis(ethylacetoacetate), and zirconium octylate compounds; and organic iron compounds such as iron tris(2,4-pentanedionato)(III).

[0048] The amount of catalyst added when introducing these polymerizable monomers having a radically polymerizable unsaturated group may be in the range of 1 to 10,000 ppm, and preferably 10 to 1,000 ppm, based on the polymerizable monomer.

[0049] During the above reaction, a polymerization inhibitor or an antioxidant can be used to suppress the polymerization reaction of the (meth)acrylate group during the reaction. Examples of polymerization inhibitors or antioxidants include, but are not limited to, hydroquinone, p-methoxyphenol, 2,6-di-tert-butyl-p-cresol, 2,4-dimethyl-6-t-butylphenol, p-benzoquinone, dibutylhydroxytoluene, 2,5-dihydroxy-p-benzoquinone, and mequinol.

[0050] As a method for producing a polyester-polyether copolymer, when a carboxy-modified polyether is used as a starting material, there can be mentioned a method in which the starting material is subjected to an esterification reaction with a poly-ε-caprolactone-modified (meth)acrylate represented by the following formula (9). Commercially available poly-ε-caprolactone modified (meth)acrylate products include, for example, PLACCEL FA2D, PLACCEL FA10L, PLACCEL FN2D, and PLACCEL FM4 (manufactured by Daicel Corporation). [ka] In general formula (9), R 7 is a hydrogen atom or a monovalent hydrocarbon group having 1 to 3 carbon atoms, and is preferably a hydrogen atom or a methyl group. v is 1≦v≦50, and preferably 1≦v≦30.

[0051] The method for producing the polyester-polyether copolymer is, for example, as follows, but is not limited to this method. To 1.0 mole of the carboxy group of the carboxy-modified polyether, 1.0 to 1.25 moles (functional group equivalent ratio) of poly-ε-caprolactone-modified (meth)acrylate (formula (9)) and 0.1 to 5.0 moles of an esterification catalyst are added and mixed, and the mixture is stirred for 10 to 30 minutes at 15 to 150° C. Optionally, 1.0 to 1.25 moles of a dehydration condensation agent is added thereto, and the mixture is reacted at 15 to 150° C. for 4 to 20 hours. After the reaction, the crude product is filtered, washed with water, and / or subjected to an adsorption treatment to remove by-products, and finally the solvent is distilled off to obtain an acrylic-modified polyester (poly-ε-caprolactone)-polyether copolymer.

[0052] The obtained polyester-polyether copolymer having at least two radically polymerizable unsaturated groups in one molecule is preferably liquid, and has a weight average molecular weight (Mw.) measured by gel permeation chromatography (GPC) in the range of preferably 100 to 100,000, more preferably 500 to 50,000. If the weight average molecular weight is less than the lower limit, the crosslink density of the elastomer in the obtained elastomer spherical / composite particles will be high, which is undesirable since it may result in poor degradability. If it is greater than the upper limit, the viscosity of the copolymer will be high, which may make it difficult to prepare the elastomer spherical particles.

[0053] In the filtration step, the crude reaction product may be diluted with a hydrophobic organic solvent for the purpose of adjusting the viscosity of the crude reaction product. The hydrophobic organic solvent to be used is not particularly limited, but from the viewpoint of solubility and affinity for the polyester-polyether copolymer, toluene, hexane, ethyl acetate, and the like are preferred.

[0054] The adsorption treatment step is carried out for the purposes of removing hydrochlorides that cannot be completely removed by washing with water, and for the purposes of dehydration, decolorization, and deodorization. The adsorbent to be used may be any conventionally known one, and a combination of multiple types may be used. Preferred adsorbents include desiccants such as magnesium sulfate and sodium sulfate, activated carbon, silica gel, and Kyoward series (manufactured by Kyowa Chemical Industry Co., Ltd.). The copolymer having a polyester structure and a polyether structure produced by the above method can be used to produce elastomer spherical particles, for example, by a method including the steps i) to iii) described below.

[0055] -Polyorganosilsesquioxane In the present invention, the polyorganosilsesquioxane on the surface of the elastomer spherical particles is R 7 SiO 3 / 2 It is a resin-like solid in which the units represented by are cross-linked in a three-dimensional network.

[0056] R in the above formula 7 R is an unsubstituted or substituted monovalent hydrocarbon group having 1 to 20 carbon atoms. 7 Examples of the alkyl group include alkyl groups such as methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, decyl, undecyl, dodecyl, tetradecyl, pentadecyl, hexadecyl, heptadecyl, octadecyl, nonadecyl, and icosyl; alkenyl groups such as vinyl and allyl; aryl groups such as phenyl, tolyl, and naphthyl; aralkyl groups such as benzyl and phenethyl; cycloalkyl groups such as cyclopentyl, cyclohexyl, and cycloheptyl; and hydrocarbon groups in which some or all of the hydrogen atoms bonded to the carbon atoms of these groups are substituted with atoms such as halogen atoms (fluorine atoms, chlorine atoms, bromine atoms, and iodine atoms) and / or substituents such as amino groups, acryloyloxy groups, methacryloyloxy groups, epoxy groups, glycidoxy groups, mercapto groups, and carboxyl groups. In order to adhere polyorganosilsesquioxane to the surface of the elastomer spherical particles by the production method of the present invention described later, 7 It is preferable that 50 mol % or more of R are methyl groups, vinyl groups, or phenyl groups.7 More preferably, 80 mol % or more of R are methyl groups, vinyl groups, or phenyl groups. 7 More preferably, 90 mol % or more of the groups are methyl, vinyl, or phenyl.

[0057] The polyorganosilsesquioxane is preferably selected from the group consisting of polyorganosilsesquioxane and polyorganosilsesquioxane, and polyorganosilsesquioxane may be used in an amount of 100% by weight, within a range that does not impair the properties of the resulting elastomer composite particles, such as non-aggregation and dispersibility, the feel when used, such as silkiness and smoothness, or the soft feel when used. 7 SiO 3 / 2 In addition to units, R 7 2SiO 2 / 2 Units, R 7 3SiO 1 / 2 Units, and SiO 4 / 2 It may contain at least one type of unit. In such polyorganosilsesquioxanes, R 7 SiO 3 / 2 The content of the unit in the total siloxane units is preferably 70 to 100 mol %, and more preferably 80 to 100 mol %.

[0058] -silica In the present invention, the silica on the surface of the elastomer spherical particles is R 8 SiO 4 / 2 It is an inorganic solid in which units represented by the formula (I) are cross-linked in a three-dimensional network.

[0059] R in the above formula 8 R is an unsubstituted or substituted monovalent hydrocarbon group having 1 to 6 carbon atoms. 8 Examples of the alkyl group include a methyl group, an ethyl group, a propyl group, a butyl group, a pentyl group, and a hexyl group.

[0060] Silica is obtained by the hydrolysis and polycondensation reaction of tetraalkoxysilane and is mainly composed of SiO2 units. Furthermore, the silica may contain not only a structure consisting of SiO2 units, but also alkoxy groups derived from the raw material tetraalkoxysilane, and silanol groups that have not undergone condensation reaction.

[0061] In the present invention, the shape of the polyorganosilsesquioxane or silica is preferably spherical. The particle size of the polyorganosilsesquioxane and silica is preferably 10 to 500 nm, and more preferably 20 to 200 nm. If the particle size of the polyorganosilsesquioxane and silica is less than 10 nm, the light scattering properties of the resulting elastomer composite particles may be reduced, whereas if the particle size of the polyorganosilsesquioxane and silica is more than 500 nm, the resulting elastomer composite particles may lack a soft feel and may also have reduced light scattering properties. The polyorganosiloxane or silica may be attached to a part of the particle surface of the elastomeric spherical particle, or may be attached over the entire particle surface, i.e., cover the entire particle surface. However, it is preferable that the polyorganosiloxane or silica is coated over the entire surface of the elastomeric spherical particle with almost no gaps. The particle size, shape, and adhesion density of polyorganosilsesquioxane and silica on the surface of the elastomer spherical particles can be confirmed by observing the particle surface of the obtained elastomer composite particles with an electron microscope. The particle size of polyorganosilsesquioxane and silica is the average value calculated by measuring the particle size of 50 randomly selected particles from an electron microscope photograph of the particle surface of the obtained elastomer composite particles.

[0062] In the elastomer composite particle of the present invention, the amount of polyorganosilsesquioxane or silica attached to the surface of the elastomer spherical particle is preferably 0.5 to 200 parts by mass, and more preferably 1.0 to 50 parts by mass, of polyorganosilsesquioxane or silica per 100 parts by mass of the elastomer spherical particle. If the amount of polyorganosilsesquioxane or silica is less than the lower limit, the particles may have high coagulation properties, poor dispersibility, reduced light scattering properties, and poor silkiness. If the amount of polyorganosilsesquioxane or silica is more than the upper limit, the elastomer composite particles may have poor softness.

[0063] [Method of manufacturing elastomer spherical particles and elastomer composite particles] The method for producing elastomer spherical particles of the present invention includes the following steps i) to iii). i) A step of preparing a suspension composition by stirring and suspending the following components (A), (B), (C), and (D): (A) A copolymer having a polymerizable group and having a polyester structure and a polyether structure (B) an aqueous phase component or an oil phase component that is insoluble or poorly soluble in the component (A) (C) Suspension (D) Polymerization initiator ii) A step of obtaining a dispersion of elastomer spherical particles by radically polymerizing the component (A) in the suspension composition obtained in the step i). iii) A process for obtaining elastomeric spherical particles by washing and drying to remove the continuous phase (B) from the dispersion of elastomeric spherical particles obtained in the process ii).

[0064] The elastomer composite particles of the present invention can be produced, for example, by a method having the following step iv). iv) A step of adding the following component (I) to a liquid phase containing the following components (E), (F), (G), and (H) and subjecting the component (I) to a hydrolysis / polymerization reaction. (E) Elastomer spherical particles having a volume average particle size of 0.5 to 200 μm, which are crosslinked copolymer particles having a polyester structure and a polyether structure, produced by the steps i) to ii) or i) to iii). (F) Alkaline substances (G) One or more selected from cationic surfactants and cationic water-soluble polymer compounds (H)Water (I) Trialkoxysilane or tetraalkoxysilane That is, the method for producing elastomer composite particles of the present invention can be roughly divided into two steps: steps i) to iii) of producing elastomer spherical particles, and step iv) of compounding the elastomer spherical particles. Each step will be explained below. The aqueous dispersion of the elastomer composite particles obtained in step iv) may be used as it is as the aqueous dispersion depending on the application, or may be subjected to a dehydration step for removing water and a powderization step to produce an elastomer composite particle powder for use in the desired application.

[0065] - Manufacturing process of elastomer spherical particles The elastomer spherical particles constituting the elastomer composite particles of the present invention are polymers (crosslinked particles) obtained by a radical polymerization reaction of the above-mentioned polyester-polyether copolymer, and are produced by a production method including the following steps i) to iii):

[0066] Process i) In step i), the following components (A), (B), (C) and (D) are stirred and suspended to prepare a suspension composition. The components used in step i) are as follows:

[0067] The component (A) is a copolymer having a polymerizable group and having a polyester structure and a polyether structure, and is preferably a polyester-polyether copolymer having a radically polymerizable unsaturated group. The constituent units of the elastomer composite particles of the present invention are derived from a copolymer having a polyester structure and a polyether structure, and preferably, a polyester-polyether copolymer having at least two radically polymerizable unsaturated groups in one molecule can be used. Specific examples of the component (A) include, for example, the polyester-polyether copolymer represented by the above general formula (1) or (2), and more preferably, the polyester-polyether copolymer represented by the above general formula (5) or (6).

[0068] The content of component (A) in the suspension composition prepared in step i) is preferably 1.0 to 80 parts by mass per 100 parts by mass of the composition. If the amount of component (A) is less than the lower limit above, production efficiency may decrease, while if it is more than the upper limit above, suspension may be insufficient, making it difficult to obtain a dispersion of the elastomer spherical particles, which is not preferred.

[0069] Component (B) is a component that becomes a continuous phase in the suspension composition, and is an aqueous phase component in which component (A) is insoluble or poorly soluble, or an oil phase component.

[0070] When component (B) is an aqueous phase component, specific examples of the water contained in the aqueous phase component include distilled water, ion-exchanged water, pure water, and ultrapure water.

[0071] The aqueous phase component may contain any additives within the range that does not impair the function of the continuous phase. Specific examples include, but are not limited to, preservatives, salts, pH adjusters, chelating agents, vitamins, amino acids, moisturizing agents, and antioxidants. In order to make the composition in which component (A) is insoluble or poorly soluble, the content of water in the aqueous phase component is preferably 90 to 100% by mass.

[0072] When component (B) is an oil phase component, examples of the oil phase component include silicone oils, hydrocarbon oils, higher fatty acids, ester oils, liquid oils, etc., which may be used alone or in appropriate combination of two or more types, but are not limited to these.

[0073] Examples of silicone oils include dimethylpolysiloxane, methylhydrogenpolysiloxane, methylphenylpolysiloxane, octamethylsiloxane, decamethyltetrasiloxane, decamethylcyclopentasiloxane, hexamethylcyclotrisiloxane, and octamethylcyclotetrasiloxane.

[0074] Examples of hydrocarbon oils include liquid paraffin, α-olefin oligomer, isododecane, isohexadecane, squalane, ozokerite, squalene, ceresin, paraffin, isoparaffin, paraffin wax, polyethylene wax, polyethylene-polypropylene wax, pristane, polyisobutylene, petrolatum, and microcrystalline wax.

[0075] Examples of higher fatty acids include lauric acid, myristic acid, palmitic acid, stearic acid, behenic acid, undecylenic acid, oleic acid, linoleic acid, linolenic acid, arachidonic acid, eicosapentaenoic acid (EPA), docosahexaenoic acid (DHA), isostearic acid, and 12-hydroxystearic acid.

[0076] Examples of ester oils include isopropyl myristate, cetyl octanoate, octyldodecyl myristate, isopropyl palmitate, butyl stearate, hexyl laurate, myristyl myristate, decyl oleate, hexyldecyl dimethyloctanoate, cetyl lactate, myristyl lactate, lanolin acetate, isocetyl stearate, isocetyl isostearate, isononyl isononanoate, cholesteryl 12-hydroxystearate, ethylene glycol di-2-ethylhexanoate, dipentaerythritol fatty acid esters, N-alkyl glycol monoisostearate, neopentyl glycol dicaprate, diisostearyl malate, glycerin di-2-heptylundecanoate, trimethylolpropane tri-2-ethylhexanoate, trimethylolpropane triisostearate, pentatetra-2-ethylhexanoate, Erythritol, glycerin tri-2-ethylhexanoate, glycerin trioctanoate, glycerin triisopalmitate, trimethylolpropane triisostearate, cetyl 2-ethylhexanoate, 2-ethylhexyl palmitate, glycerin trimyristate, tri-2-heptylundecanoate glyceride, castor oil fatty acid methyl ester, oleyl oleate, acetoglyceride, 2-hexyl palmitate butylundecyl, diisobutyl adipate, N-lauroyl-L-glutamic acid-2-octyldodecyl ester, di-2-heptylundecyl adipate, ethyl laurate, di-2-ethylhexyl sebacate, 2-hexyldecyl myristate, 2-hexyldecyl palmitate, 2-hexyldecyl adipate, diisopropyl sebacate, 2-ethylhexyl succinate, triethyl citrate, and the like.

[0077] Examples of liquid oils and fats include avocado oil, camellia oil, turtle oil, macadamia nut oil, corn oil, mink oil, olive oil, rapeseed oil, egg yolk oil, sesame oil, persic oil, wheat germ oil, sasanqua oil, castor oil, linseed oil, safflower oil, cottonseed oil, perilla oil, soybean oil, peanut oil, tea seed oil, kaya oil, rice bran oil, Chinese tung oil, Japanese tung oil, jojoba oil, germ oil, and triglycerin.

[0078] Component (B) has a kinetic viscosity of 100,000mm at 25°C. 2 / s or less is preferable, and 10,000 mm 2 If the kinetic viscosity is greater than the above upper limit, suspension in step i) becomes difficult, and it may become difficult to obtain a suspension composition and elastomer spherical particles having a narrow particle size distribution.

[0079] Examples of the suspending agent of component (C) include water-soluble polymer compounds such as conventionally known natural polymer compounds, semisynthetic polymer compounds, and synthetic polymer compounds, or polymer compounds used as thickeners. These may be used alone or in appropriate combination of two or more.

[0080] Examples of natural polymeric compounds include xanthan gum, cellulose, tamarind gum, tamarind seed gum, locust bean gum, gellan gum, HM pectin, carrageenan, guar gum, amas seed gum, gum arabic, pullulan, agarose, agaropectin, alginic acid, karaya gum, succinoglycan, starch, dextrin, gelatin, and casein.

[0081] Examples of semi-synthetic polymer compounds include methyl cellulose, ethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, hydroxypropyl methyl cellulose, carboxymethyl cellulose, cationized xanthan gum, LM pectin (acid-treated / alkali-treated), cationized guar gum, alginates, soluble starch, and cellulose nanofibers.

[0082] Examples of synthetic polymer compounds include polyvinyl alcohol, polyvinyl methyl ether, polyvinylpyrrolidone, carboxyvinyl polymer, polyacrylic acid, sodium polyacrylate, ammonium polyacrylate, polyacrylic acid amide, polyethylene glycol, polypropylene glycol, and polyethylene-polypropylene glycol.

[0083] As the component (C), from the viewpoints that a small amount of the component (A) can be suspended and fine elastomeric spherical particles can be obtained, the following are preferred: xanthan gum, tamarind gum, carrageenan, guar gum, gum arabic, methyl cellulose, ethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, hydroxypropyl methyl cellulose, carboxymethyl cellulose, cationized xanthan gum, cationized guar gum, polyvinyl alcohol, and polyvinylpyrrolidone.

[0084] The amount of component (C) added is preferably 0.01 to 25 parts by mass, more preferably 0.05 to 15 parts by mass, per 100 parts by mass of the suspension composition. If the amount is less than the lower limit, emulsification may be insufficient or fine elastomer spherical particles may not be obtained, which is not preferred. If the amount is more than the upper limit, the viscosity of the composition may increase significantly, making it difficult to obtain fine elastomer spherical particles and resulting in insufficient particle dispersibility, which is not preferred.

[0085] As the polymerization initiator of component (D), a conventionally known radical polymerization initiator may be used. In the presence of the polymerization initiator, an external stimulus such as heating, light irradiation, or UV irradiation is applied to generate radicals, which can cause reaction and curing (crosslinking).

[0086] Specific examples of the polymerization initiator (D) that can be used include peroxides, azo-based initiators, photoinitiators, and redox-based initiators that combine an oxidizing agent and a reducing agent.

[0087] Examples of peroxides include benzoyl peroxide, 2,4-dichlorobenzoyl peroxide, o-methylbenzoyl peroxide, p-methylbenzoyl peroxide, 2,4-dicumyl peroxide, 2,5-dimethyl-2,5-di(t-butylperoxy)hexane, di-t-butyl peroxide, t-butyl perbenzoate, and hydrogen peroxide. Moreover, perchlorates such as potassium perchlorate and sodium perchlorate may also be used.

[0088] Examples of azo initiators include 2,2'-azobis-isobutyronitrile, 2,2'-azobis-(2-methylbutyronitrile), 2,2'-azobis-(2,4-dimethylvaleronitrile), dimethyl 2,2'-azobis-(2-methylpropionate), dimethyl 2,2'-azobis-isobutyrate, t-butylperoxy-2-ethylhexanoate, 2,2-azobis-(2-aminodipropane) dihydrochloride, and the like.

[0089] Examples of photoinitiators include 2,2-diethoxyacetophenone, 2,2-dimethoxy-1,2-diphenylethan-1-one, 1-hydroxy-cyclohexyl phenyl ketone, 2-hydroxy-2-methyl-1-phenylpropan-1-one, 2-hydroxy-1-{4-[4-(2-hydroxy-2-methylpropionyl)benzyl]phenyl}-2-methylpropan-1-one, phenylglyoxylic acid methyl ester, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropan-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-1-butanone, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, (2,4,6-trimethylbenzoyl)-diphenylphosphine oxide, and the like. Benzoin alkyl ethers such as benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, and benzoin isobutyl ether can also be used.

[0090] Examples of the redox initiator include a combination of ferrous sulfate / sodium pyrophosphate / glucose / hydroperoxide, and a combination of ferrous sulfate / disodium ethylenediaminetetraacetate / Rongalite / hydroperoxide. The redox initiator may be used in combination with an azo initiator or a photoinitiator.

[0091] As the polymerization initiator, from the viewpoints of stability during the (radical) polymerization reaction of the suspension composition, ease of handling, and the like, peroxides, azo-based initiators, and photoinitiators used in the heating method or light irradiation method are preferred.

[0092] The polymerization initiator is preferably added in an amount within the range of 0.01 to 5.0 parts by mass per 100 parts by mass of the component (A). If the amount of polymerization initiator added is less than the lower limit, curing (crosslinking) may be poor. If the amount is more than the upper limit, contamination with reaction residues or the like may occur, which is not preferable.

[0093] Other Additives In the method for producing elastomer composite particles of the present invention, when preparing the suspension composition in step i), various additives may be added, if necessary, in addition to the above-mentioned components (A), (B), (C), and (D). Examples of additives include thickeners, pH adjusters, preservatives, antioxidants, polymerization inhibitors, etc., and each of them can be used alone or in appropriate combination of two or more kinds in an appropriate amount within a range that does not impair the effects of the present invention.

[0094] The order of adding and mixing the respective components in step i) is not particularly limited. For example, the components (A) and (D) may be mixed in advance, and then the components (B) and (C) may be added to prepare a suspension composition. Alternatively, a suspension composition may be prepared from the components (A), (B), and (C), and then the component (D) may be added. In addition, after preparing a suspension composition from the components (A), (B), (C), and (D), the suspension composition may be diluted by further adding the component (B) to a desired concentration before being subjected to step ii).

[0095] In addition, when the polyester-polyether copolymer having a radically polymerizable unsaturated group, component (A), has a cloud point (when heated, the solubility of component (A) decreases rapidly at a certain temperature, resulting in phase separation), or has temperature dependency, the suspension composition in step i) may be prepared at a temperature according to the temperature characteristics of component (A), for example, by stirring and suspending while heating. The temperature conditions during warming / heating are, for example, 100° C. or lower, preferably 30 to 90° C., and more preferably in the range of 40 to 70° C. When the continuous phase is an aqueous phase component, it is not preferable for the temperature during warming / heating to be higher than the above upper limit value, since there is a risk of water evaporation or bumping.

[0096] In preparing the suspension composition in step i), a conventionally known emulsifying and dispersing machine may be used. Examples of common emulsifying and dispersing machines include high-speed rotary shear type agitators such as homomixers, high-speed centrifugal radial type agitators such as homodisper, combimix emulsifying and dispersing machines combining homomixers and homodisper, mixing and emulsifying agitators (adiphommixers) combining homomixers or homodisper and anchor mixers, high-pressure jet type emulsifying and dispersing machines such as homogenizers, colloid mills, ultrasonic emulsifiers, and propeller agitators.

[0097] Process ii) Step ii) is a step of reacting and curing (crosslinking) the component (A) in the suspension composition prepared in step i) by (radical) polymerization to obtain a dispersion of elastomer spherical particles.

[0098] In step ii), the conditions for the polymerization reaction can be appropriately determined depending on the type of the polymerization initiator (D). For example, when a peroxide or azo-based initiator is used, a heating method in which the reaction is carried out for 10 to 24 hours at a temperature of 30 to 80° C. can be used, and when a redox-based initiator is used, a redox method in which the reaction is carried out for 2 to 24 hours at a temperature of 30 to 70° C. can be used. When a photoinitiator is used, a photoirradiation method in which the reaction is carried out under light irradiation can be used, and the light source and wavelength range used for light or UV irradiation may be any of those known in the art.

[0099] Process iii) Step iii) is a step of obtaining elastomeric spherical particles by washing, drying and removing the continuous phase (B) component from the dispersion of elastomeric spherical particles obtained in step ii).

[0100] When the continuous phase (dispersion medium) of component (B) is an aqueous phase component, specific methods for step iii) include concentrating the dispersion by methods such as heat dehydration, (pressure) filtration, centrifugation, and decantation, and then adding pure water or the like as necessary to perform a water washing operation. Finally, examples include a method of drying by heating under normal pressure or reduced pressure, a method of spraying the dispersion in a heated air stream and drying by heating (spray drying), a method of drying by heating using a fluidized heat medium, or a freeze drying method in which the dispersion is solidified, then reduced pressure is applied, and the dispersion medium is removed, thereby obtaining elastomeric spherical particles. If the elastomeric spherical particles obtained by washing and drying to remove the dispersion medium are aggregated, they may be crushed using a mortar, ball mill, jet mill, or the like.

[0101] When the continuous phase (dispersion medium) of component (B) is an oil phase component, a specific method for step iii) is, for example, to add a hydrophobic organic solvent to a dispersion of elastomer spherical particles, stir for a certain period of time, and then perform pressure filtration to wash and remove component (B) and replace the solvent. By repeating this washing operation several times, component (B) can be sufficiently removed and the solvent can be replaced. Examples of hydrophobic organic solvents used in this case include toluene and hexane. Finally, elastomer spherical particles are obtained by performing a method of drying by heating under normal pressure or reduced pressure, a method of spraying the dispersion in a heated air stream and drying by heating (spray drying), a method of drying by heating using a fluidized heat medium, or a freeze drying method in which the dispersion is solidified, then reduced pressure is applied, and the dispersion medium is removed. The elastomer spherical particles produced by the method having the above steps i) to iii) are fine particles having a volume average particle size in the range of 0.5 to 200 μm, more preferably 1.0 to 50 μm. Therefore, the elastomer spherical particles obtained by the method for producing elastomer spherical particles of the present invention can be particularly suitably used for producing the elastomer composite particles of the present invention.

[0102] - Manufacturing process of elastomer composite particles (resin or silica coated elastomer spherical particles) Process iv) Step iv) is a step of adding the following component (I) to a liquid phase containing the following components (E), (F), (G), and (H) to subject the component (I) to a hydrolysis and polymerization reaction.

[0103] As the elastomer spherical particles of the component (E), the elastomer spherical particles obtained in the above-described steps i) to ii) or i) to iii) are used. When the component (B) used in step i) is an aqueous phase component, the aqueous dispersion of the elastomer spherical particles obtained in steps i) and ii) may be subjected to step iv) as a mixture of the components (E) and (H) without going through the above step iii).

[0104] The amount of the (E) elastomer spherical particles is preferably 1.0 to 150 parts by mass, more preferably 3.0 to 70 parts by mass, per 100 parts by mass of (H) water in the liquid phase containing (E) to (H). If the amount of the (E) component is less than the above lower limit, the production efficiency of the intended elastomer composite particles may decrease, and if it is more than the above upper limit, it is difficult to coat the surfaces of the elastomer spherical particles with polyorganosilsesquioxane or silica, which may cause aggregation or fusion of the particles, which is not preferable.

[0105] (F) The alkaline substance acts as a catalyst for the hydrolysis and polycondensation reaction of trialkoxysilane or tetraalkoxysilane. The alkaline substance may be used alone or in appropriate combination of two or more kinds.

[0106] The alkaline substance is not particularly limited, and examples thereof include alkali metal hydroxides such as potassium hydroxide, sodium hydroxide, and lithium hydroxide; alkaline earth metal hydroxides such as calcium hydroxide and barium hydroxide; alkali metal carbonates such as potassium carbonate and sodium carbonate; ammonia; tetraalkylammonium hydroxides such as tetramethylammonium hydroxide and tetraethylammonium hydroxide; amines such as monomethylamine, monoethylamine, monopropylamine, monobutylamine, monopentylamine, dimethylamine, diethylamine, trimethylamine, triethanolamine, and ethylenediamine. These alkaline substances may be used alone or in appropriate combination of two or more.

[0107] The most preferable alkaline substance is ammonia, since it can be easily removed from the powder of the elastomer composite particles obtained by volatilization. As the ammonia, commercially available aqueous ammonia solutions of various concentrations may be used.

[0108] The amount of alkaline substance (F) added is preferably an amount that gives a liquid phase containing components (E) to (H) a pH of 9.0 to 13.0 at 25° C., more preferably an amount that gives a pH in the range of 10.0 to 12.0. Adding an amount that gives a pH of 9.0 to 13.0 allows the hydrolysis and polycondensation reaction of trialkoxysilane or tetraalkoxysilane to proceed satisfactorily, and the surfaces of the elastomer spherical particles are sufficiently coated with resin or silica.

[0109] (G) Cationic surfactants and cationic water-soluble polymeric compounds have the effect of accelerating the condensation reaction of hydrolyzed trialkoxysilanes or tetraalkoxysilanes to produce resins or silica. They also have the effect of adsorbing the produced resins or silica to the surfaces of the elastomer spherical particles. The cationic surfactants and cationic water-soluble polymeric compounds can be used alone or in appropriate combination of two or more.

[0110] Examples of cationic surfactants include alkyltrimethylammonium salts, dialkyldimethylammonium salts, polyoxyethylenealkyldimethylammonium salts, dipolyoxyethylenealkylmethylammonium salts, tripolyoxyethylenealkylammonium salts, alkylbenzyldimethylammonium salts, alkylpyridinium salts, monoalkylamine salts, and monoalkylamidoamine salts.

[0111] Examples of the cationic water-soluble polymer compound include polymers of dimethyldiallylammonium chloride, polymers of vinylimidazoline, polymers of methylvinylimidazolium chloride, polymers of ethyltrimethylammonium chloride acrylate, polymers of ethyltrimethylammonium chloride methacrylate, polymers of acrylamidopropyltrimethylammonium chloride, polymers of methacrylamidopropyltrimethylammonium chloride, epichlorohydrin / dimethylamine polymers, polymers of ethyleneimine, quaternary products of ethyleneimine polymers, polymers of allylamine hydrochloride, polylysine, cationic starch, cationic cellulose, chitosan, and copolymers of these with monomers having a nonionic group or anionic group, and derivatives thereof.

[0112] As the component (G), alkyltrimethylammonium salts of cationic surfactants are preferred, and among these, lauryltrimethylammonium salts and cetyltrimethylammonium salts are more preferred.

[0113] The amount of cationic surfactant and cationic water-soluble polymer compound added is preferably 0.01 to 2.0 parts by mass, more preferably 0.1 to 1.0 parts by mass, per 100 parts by mass of water in the liquid phase containing (E) to (H). If the amount of component (G) added is less than the above lower limit, resin or silica that is not coated on the surface of the elastomeric spherical particles may be formed, and if the amount added is more than the above upper limit, resin or silica that is not coated on the surface of the elastomeric spherical particles may be formed.

[0114] The water (H) is not particularly limited, and may be, for example, purified water, ion-exchanged water, pure water, etc. In the case where the component (B) is an aqueous phase component and the aqueous dispersion of the elastomer spherical particles obtained in the step ii) is subjected to the step iv) without going through the above step iii), the water (H) includes the water in the aqueous dispersion and water added as necessary.

[0115] (I) The trialkoxysilane and tetraalkoxysilane are not particularly limited, and conventionally known ones may be used, and from the viewpoint of reactivity, methyltrimethoxysilane, methyltriethoxysilane, tetramethoxysilane, and tetraethoxysilane are preferred, and methyltrimethoxysilane and tetramethoxysilane are more preferred. The tetraalkoxysilane may be one in which a part or all of the alkoxy groups are hydrolyzed, or one in which a part is condensed.

[0116] The amount of trialkoxysilane added is preferably such that the amount of polyorganosilsesquioxane is 1.0 to 50 parts by mass, and more preferably 2 to 25 parts by mass, per 100 parts by mass of the (E) elastomer spherical particles. The amount of tetraalkoxysilane added is preferably such that the amount of silica is 0.5 to 200 parts by mass, more preferably 1.0 to 50 parts by mass, per 100 parts by mass of the (E) elastomer spherical particles.

[0117] Hydrolysis and polycondensation reaction (I) a trialkoxysilane or a tetraalkoxysilane is added to a liquid phase containing (E) to (H), and these are subjected to a hydrolysis / polycondensation reaction. Specifically, (E) elastomer spherical particles are dispersed in (H) water, and (I) trialkoxysilane or tetraalkoxysilane is added to the aqueous dispersion in which (F) alkaline substance, (G) cationic surfactant, and one or more selected from cationic water-soluble polymer compounds are dissolved, and hydrolysis and polycondensation are carried out. By the hydrolysis and polycondensation, polyorganosilsesquioxane or silica is attached to the surface of the elastomer spherical particles as a condensation product of trialkoxysilane or tetraalkoxysilane, and the surface of the elastomer spherical particles is thereby coated with polyorganosilsesquioxane or silica.

[0118] The trialkoxysilane and tetraalkoxysilane are preferably added under stirring using a normal stirrer such as a propeller blade or flat blade. They may be added all at once, but it is preferable to add them over a period of time. The dropwise addition time is preferably in the range of 1 minute to 6 hours, more preferably 10 minutes to 3 hours.

[0119] The temperature of the liquid phase at this time is preferably in the range of 0 to 60° C., and more preferably in the range of 0 to 40° C. If the temperature is within the above range, the polyorganosilsesquioxane or silica can be successfully attached to and coated on the surfaces of the elastomer spherical particles in the liquid phase. Stirring is continued after the addition of trialkoxysilane or tetraalkoxysilane until the hydrolysis and polycondensation reactions are completed. To complete the hydrolysis and polycondensation reactions, the reaction may be carried out at room temperature or under heating at about 40 to 100°C, and an alkaline substance may be added as appropriate.

[0120] Dehydration process / Powderization process After the hydrolysis and polycondensation reaction in step iv), water is optionally removed from the aqueous dispersion of the elastomer composite particles of the present invention obtained by heating the aqueous dispersion after the reaction under normal pressure or reduced pressure. Specifically, examples of the method include a method of heat drying under normal pressure or reduced pressure, a method of spraying the dispersion liquid into a heated air current and heat drying (spray drying), a method of heat drying using a fluid heat medium, and a freeze drying method in which the dispersion liquid is solidified, then reduced pressure is applied and the dispersion medium is removed, and the like are used, and thus elastomer composite particles are obtained. As a pretreatment step for this operation, the dispersion may be concentrated by a method such as heating for dehydration, filtration, centrifugation, or decantation, and the aqueous dispersion may be washed with water or alcohol, if necessary.

[0121] When the powder of the elastomer composite particles obtained by removing water from the aqueous dispersion after the reaction is aggregated, the aggregated powder may be disintegrated by a pulverizer such as a jet mill, a ball mill, or a hammer mill. EXAMPLES

[0122] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to the following examples. In the following examples, unless otherwise specified, "%" and "parts" indicating concentration and content refer to "% by mass" and "parts by mass", respectively. The kinetic viscosity is a value measured at 25°C. In the following examples, the volume average particle size and aspect ratio of the elastomer spherical particles and elastomer composite particles are values ​​measured by the above-mentioned methods. The hardness of the cured rubber (elastomer) is a value measured in accordance with the Standards of the Society of Rubber Industry, Japan (SRIS).

[0123] The molecular weight of a copolymer having a polyester structure and a polyether structure (a polyester-polyether copolymer having at least two radically polymerizable unsaturated groups in one molecule) is the weight average molecular weight (Mw.) measured by GPC under the following conditions using polystyrene as the standard substance. [Measurement conditions] Developing solvent: Tetrahydrofuran (THF) Flow rate: 0.60mL / min. Detector: Refractive index detector (RI) Column: TSK Guardcolumn SuperH-H, TSKgel SuperHM-N, TSKgel SuperH2500 (both manufactured by Tosoh Corporation) Column temperature: 40℃ Sample injection volume: 50 μL (THF solution with a concentration of 0.5% by mass)

[0124] [Measurement and evaluation method for biodegradability] Biodegradability was measured using a method using activated sludge as a microbial (degradation) source in accordance with OECD Guidelines for the Testing of Chemicals, No.301F, July 17, 1992, "Ready Biodegradability: MANOMETRIC RESPIROMETRY TEST," and was evaluated based on the degree of biodegradability. Activated sludge used was from a municipal sewage treatment plant, and the suspended solids concentration was 2,400 mg / L. Sodium benzoate was used as the standard (control) substance. The degree of biodegradation is measured by measuring the amount of oxygen consumed (biochemical oxygen consumption (BOD)) in a closed system inside an incubator using a BOD meter, and calculating the degree of biodegradation based on the following formula. Biodegradability (%)=BOD-B / TOD×100 BOD: Biochemical oxygen consumption of the test suspension or control (measured value: mg) B: Average biochemical oxygen consumption of the plant source blank (measured in mg) TOD: Theoretical oxygen consumption required for complete oxidation of the test substance or sodium benzoate (calculated value: mg)

[0125] [Synthesis of acrylic modified poly-ε-caprolactone / polyether copolymer 1 - Synthesis Example 1] A 2L separable flask equipped with a stirrer, a thermometer, a condenser, and a dropping funnel was charged with 500g of primary-terminated EO (ethylene oxide) / PO (propylene oxide) polyether (molecular weight: about 2,000, OH group equivalent: 0.09-0.10 mol / 100g), 183.6g of ε-caprolactone (molecular weight: 114.1), and 350g of dehydrated toluene, and heated to 90°C under nitrogen flow. After reaching the target temperature, 0.68g of tetra-n-butoxytitanium (molecular weight: 340.0) was added as a catalyst, and the mixture was aged at 120°C for 4 to 6 hours. Next, the poly-ε-caprolactone / polyether copolymer obtained by the above operation was cooled to near room temperature, and then 60.7 g of triethylamine (molecular weight 101.2), 100 g of dehydrated toluene, and 0.22 g of dibutylhydroxytoluene (BHT) (molecular weight 220.4) as a polymerization inhibitor were added, and the mixture was stirred for a certain period of time to dissolve uniformly. Then, 49.7 g of acrylic acid chloride (molecular weight 90.5) was added dropwise using a dropping funnel, and after confirming the generation of heat, the mixture was aged at 60° C. for 4 hours. The obtained crude product was filtered under pressure, washed with an aqueous sodium chloride solution using a separating funnel, centrifuged, etc., and then magnesium sulfate, silica gel, activated carbon, etc. were added and powder treatment was performed by shaking to adsorb and remove impurities. After removing the various powders by pressure filtration, 0.22 g of dibutylhydroxytoluene (BHT) was added again, and the solvent was distilled off under conditions of 60 to 70°C and 50 mmHg or less to obtain an acrylic-modified poly-ε-caprolactone / polyether copolymer 1 (formula (11) below, weight average molecular weight: 2,880). [ka]

[0126] [Synthesis of acrylic modified poly-ε-caprolactone / polyether copolymer 2 - Synthesis Example 2] In a 1 L separable flask equipped with a stirrer, a thermometer, a condenser, and a dropping funnel, 300 g of the same primary-terminated EO / PO polyether as in Synthesis Example 1, 110.2 g of ε-caprolactone, and 200 g of dehydrated toluene were charged and heated to 90°C under a nitrogen flow. After reaching the target temperature, 0.41 g of tetra-n-butoxytitanium was added as a catalyst, and the mixture was aged at 120°C for 4 to 6 hours. Next, the poly-ε-caprolactone / polyether copolymer obtained by the above operation was cooled to about room temperature, and then 100 g of dehydrated toluene, 0.96 g of dioctyltin dineodecanoate (molecular weight: 687.7) as a catalyst, and 0.12 g of dibutylhydroxytoluene (BHT) were added thereto, and the mixture was stirred for a certain period of time to dissolve uniformly. Then, 44.4 g of 2-isocyanatoethyl acrylate (molecular weight: 141.1) was added dropwise using a dropping funnel, and after confirming the generation of heat, the mixture was aged at 60° C. for 4 hours. The obtained crude product was cooled to 40°C or less, and then 0.8 g of ethanol was added to react with the unreacted (residual) isocyanate groups for quenching treatment. Next, magnesium sulfate, silica gel, activated carbon, etc. were added, and powder treatment was performed by shaking to adsorb and remove impurities. After removing the various powders by pressure filtration, 0.12 g of dibutylhydroxytoluene (BHT) was added again, and the solvent was distilled off under conditions of 60 to 70°C and 50 mmHg or less to obtain an acrylic-modified poly-ε-caprolactone / polyether copolymer 2 (formula (12) below, weight average molecular weight: 3,120). [ka]

[0127] [Synthesis of acrylic modified poly-ε-caprolactone / polyether copolymer 3 - Synthesis Example 3] In a 1L separable flask equipped with a stirrer, a thermometer, a condenser, and a dropping funnel, 300g of primary-terminated EO / PO polyether (molecular weight: about 2,600, OH group equivalent: 0.09-0.10 mol / 100g), 115.2g of ε-caprolactone, and 200g of dehydrated toluene were charged and heated to 90°C under a nitrogen flow. After reaching the target temperature, 0.42g of tetra-n-butoxytitanium was added to the catalyst and aged at 120°C for 4-6 hours. Next, the poly-ε-caprolactone / polyether copolymer obtained by the above operation was cooled to around room temperature, and then 70 g of dehydrated toluene, 0.18 g of tris(2,4-pentanedionato)iron(III) (also known as iron(III) acetylacetonate, molecular weight: 353.2) as a catalyst, and 0.13 g of dibutylhydroxytoluene (BHT) were added thereto, and the mixture was stirred for a certain period of time to dissolve uniformly. Then, 46.4 g of 2-isocyanatoethyl acrylate was added dropwise using a dropping funnel, and after confirming the generation of heat, the mixture was aged at 60°C for 4 hours. The obtained crude product was subjected to post-treatment and purification steps in the same manner as in Synthesis Example 2 above, to obtain acrylic-modified poly-ε-caprolactone / polyether copolymer 3. Acrylic-modified poly-ε-caprolactone / polyether copolymer 3 had a structure represented by formula (12), in which l was approximately 18-21, m was approximately 34-38, r was approximately 3-4, and the weight average molecular weight was 4,870.

[0128] [Synthesis of acrylic modified poly-ε-caprolactone / polyether copolymer 4 - Synthesis Example 4] In a 1 L separable flask equipped with a stirrer, a thermometer, a condenser, and a dropping funnel, 300 g of the same primary-terminated EO / PO polyether as in Synthesis Example 3, 115.2 g of ε-caprolactone, and 200 g of dehydrated toluene were charged and heated to 90°C under a nitrogen flow. After reaching the target temperature, 0.42 g of tetra-n-butoxytitanium was added as a catalyst, and the mixture was aged at 120°C for 4 to 6 hours. Next, the poly-ε-caprolactone / polyether copolymer obtained by the above operation was cooled to about room temperature, and then 70 g of dehydrated toluene, 2.77 g of zirconium tetraacetylacetonate (molecular weight: 487.7) as a catalyst, and 0.13 g of dibutylhydroxytoluene (BHT) were added thereto, and the mixture was stirred for a certain period of time to dissolve uniformly. Then, 46.4 g of 2-isocyanatoethyl acrylate was added dropwise using a dropping funnel, and after confirming the generation of heat, the mixture was aged at 60° C. for 4 hours. The obtained crude product was subjected to post-treatment and purification steps in the same manner as in Synthesis Example 2 above, to obtain acrylic-modified poly-ε-caprolactone / polyether copolymer 4. Acrylic-modified poly-ε-caprolactone / polyether copolymer 4 had a structure represented by formula (12), in which l was approximately 18-21, m was approximately 34-38, r was approximately 3-4, and the weight average molecular weight was 4,990.

[0129] [Synthesis of acrylic modified poly-ε-caprolactone / polyether copolymer 5 - Synthesis Example 5] In a 1L separable flask equipped with a stirrer, a thermometer, a condenser, and a dropping funnel, 300g of primary-terminated EO / PO polyether (molecular weight: about 3,200, OH group equivalent: 0.062mol / 100g), 106.3g of ε-caprolactone, and 200g of dehydrated toluene were charged and heated to 90°C under a nitrogen flow. After reaching the target temperature, 0.41g of tetra-n-butoxytitanium was added as a catalyst and the mixture was aged at 120°C for 4 to 6 hours. Next, the poly-ε-caprolactone / polyether copolymer obtained by the above operation was cooled to about room temperature, and then 70 g of dehydrated toluene, 1.01 g of dioctyltin dineodecanoate as a catalyst, and 0.13 g of dibutylhydroxytoluene (BHT) were added thereto, and the mixture was stirred for a certain period of time to dissolve uniformly. Then, 28.4 g of 2-isocyanatoethyl acrylate was added dropwise using a dropping funnel, and after confirming the generation of heat, the mixture was aged at 60° C. for 4 hours. The obtained crude product was subjected to post-treatment and purification steps in the same manner as in Synthesis Example 2, to obtain acrylic-modified poly-ε-caprolactone / polyether copolymer 5 (formula (13), weight average molecular weight: 7,940). [ka]

[0130] [Synthesis of acrylic modified poly-ε-caprolactone / silicone copolymer - Synthesis Example 6] A 1-L separable flask equipped with a stirrer, a thermometer, a condenser, and a dropping funnel was charged with 300 g of carboxy-modified silicone (molecular weight: approximately 1,200, COOH group equivalent: 0.19 mol / 100 g), 202.8 g of poly-ε-caprolactone monoacrylate (OH group equivalent: 0.29 mol / 100 g, molecular weight: 344.0), 200 g of dehydrated toluene, and 6.85 g of 4-dimethylaminopyridine (DMAP) (molecular weight: 122.2), and the mixture was stirred and mixed in an ice bath. After cooling sufficiently, a solution of 168.9 g of N,N'-dicyclohexylcarbodiimide (DCC) (molecular weight: 206.3) dissolved in 173.6 g of dehydrated toluene was added using a dropping funnel, and the mixture was reacted and aged for 20 hours at room temperature. After aging, the mixture was washed with 200 g of toluene and 300 g of 0.5 mol / L hydrochloric acid (to remove DMAP), and then washed with a saturated aqueous solution of sodium bicarbonate and a 10% aqueous solution of sodium chloride in that order. After carrying out the above operations, magnesium sulfate, silica gel, activated carbon, and Kyoward 700 (Kyowa Chemical Industry Co., Ltd.) were added and the mixture was shaken to adsorb and remove impurities. After removing the above-mentioned various powders by pressure filtration, 0.09 g of dibutylhydroxytoluene (BHT) was added, and the solvent was distilled off under conditions of 60 to 70°C and 10 mmHg or less, to obtain an acrylic-modified poly-ε-caprolactone / silicone copolymer (formula (14) below, weight average molecular weight: 2,130). [ka]

[0131] [Production of elastomer spherical particles - Production Example 1] 250 g of a 2.6% aqueous solution of hydroxypropyl methylcellulose (product name: Metrose 60SH-4,000, manufactured by Shin-Etsu Chemical Co., Ltd.) was charged into a 1 L container of an Adihomomister, and stirred and mixed under heating at 55 to 60°C while operating the homomixer and anchor mixer. At the same time, 100 g of the acrylic-modified poly-ε-caprolactone / polyether copolymer 4 of Synthesis Example 4 described above and 1.0 g of dimethyl 2,2'-azobis-(2-methylpropionate) (molecular weight: 230.3) were charged in a descup, premixed in a disperser mixer, and preheated to 60 to 65°C. Next, the premixed acrylic-modified poly-ε-caprolactone / polyether copolymer was added to a 1 L adipomixer containing a heated aqueous solution of hydroxypropylmethylcellulose, and the mixture was stirred and suspended for 10 minutes or more at a heating temperature of 55 to 60°C with a homomixer rotation speed of 4,500 rpm to obtain an O / W type suspension composition. The resulting suspension composition was then stirred and aged for 8 hours at 70°C at a rotation speed of 200 rpm using a paddle-type stirring blade, 50 g of pure water was added, and the mixture was further aged for 6 hours at 80°C at the same rotation speed to obtain a dispersion of elastomer spherical particles.

[0132] The shape of the elastomer spherical particles in the obtained dispersion was observed under an optical microscope and found to be spherical. The volume average particle size was measured using an electrical resistance particle size distribution measuring device (Multisizer 3, Beckman Coulter, Inc.) and found to be 5 μm.

[0133] The obtained dispersion of elastomer spherical particles was checked for the presence or absence of agglomerates by mesh filtration (#100). If agglomerates were found, they were removed, and then the continuous phase, pure water, was removed by solid-liquid separation by pressure filtration. The above washing and separation operation was repeated three times with pure water to remove water. If solid-liquid separation was not performed well in the pressure filtration process, centrifugation may be used. Finally, the concentrated elastomer spherical particles obtained above were allowed to stand and dry for 8 hours or more to obtain the target elastomer spherical particles as a white to pale yellow powder.

[0134] The obtained powder of elastomer spherical particles was observed using an electron microscope (scanning microscope S-4700, manufactured by Hitachi High-Technologies Corporation), and it was confirmed that the particles were spherical particles with a particle size of about 5 μm. The aspect ratio of the obtained elastomer spherical particles was 1.0. In addition, the obtained elastomer spherical particles were redispersed in water using polyoxyethylene lauryl ether as a surfactant, and the dispersion was measured and evaluated by an electrical resistance method, confirming that the volume average particle size was 5 μm.

[0135] The hardness of the elastomer (rubber) constituting the elastomer spherical particles was measured as follows. 30 g of the synthesized acrylic modified poly-ε-caprolactone / polyether copolymer 4 and 0.24 g of 2'-azobis-(2,4-dimethylvaleronitrile) (molecular weight: 248.4) were stirred and mixed, and poured into an aluminum petri dish to a thickness of 10 mm. After leaving it to stand for 1 to 2 hours in an air thermostatic chamber at 70°C, a flat rubber with no stickiness (tack) was obtained. The rubber hardness of the obtained flat rubber was measured, and it was 72 on the Asker C hardness scale and 55 on the Asker A hardness scale.

[0136] [Production of elastomer spherical particles - Production Example 2] Elastomer spherical particles were produced in the same manner as in Production Example 1, except that 173 g of a 3.8% aqueous solution of hydroxypropyl methylcellulose was used instead of 250 g of the 2.6% aqueous solution of hydroxypropyl methylcellulose in Production Example 1. As a result, elastomer spherical particles with a volume average particle size of 2 μm were obtained.

[0137] [Production of elastomer spherical particles - Production Example 3] Elastomer spherical particles were produced in the same manner as in Production Example 1, except that the hydroxypropyl methylcellulose (trade name: Metolose 60SH-4,000, manufactured by Shin-Etsu Chemical Co., Ltd.) was used instead (trade name: Metolose 60SH-50, manufactured by Shin-Etsu Chemical Co., Ltd.). As a result, elastomer spherical particles having a volume average particle size of 11 μm were obtained.

[0138] [Production of elastomer spherical particles - Production Example 4] Elastomer spherical particles were produced in the same manner as in Production Example 1, except that 250 g of a 5.2% aqueous solution of xanthan gum was used instead of 250 g of a 2.6% aqueous solution of hydroxypropyl methylcellulose (trade name: Metolose 60SH-4,000, manufactured by Shin-Etsu Chemical Co., Ltd.). As a result, elastomer spherical particles having a volume average particle size of 20 μm were obtained.

[0139] [Production of Elastomer Composite Particles - Example 1] In a 500 ml glass flask equipped with a stirrer using a paddle-type stirring blade, 100 g of the dispersion of elastomer spherical particles having a solid content of 20% obtained in Production Example 1, 184.9 g of pure water, and 0.2 g of a 30% aqueous solution of lauryltrimethylammonium chloride were charged. After adjusting the temperature of the aqueous dispersion to 5 to 10°C, 0.75 g of 5.0% ammonia water was added, and while maintaining the aqueous dispersion at 5 to 10°C, 11.2 g of tetramethoxysilane (an amount that would result in 22.0 parts of silica after hydrolysis and polycondensation reaction per 100 parts of elastomer spherical particles) was dropped over 15 to 30 minutes, during which the liquid temperature was maintained at 5 to 10°C and stirring was performed for 1 hour. The mixture was then heated to 55-60°C, and stirred and aged for 1 hour while maintaining the temperature, to complete the hydrolysis and condensation reaction of tetramethoxysilane.

[0140] The dispersion, which was prepared by hydrolysis and condensation reaction of tetramethoxysilane in a dispersion of elastomer spherical particles, was dehydrated to about 30% water using a pressure filter. The dehydrated product was then transferred to a 1L glass flask equipped with an anchor-shaped stirring blade stirrer, 500g of water was added, and the mixture was stirred for 30 minutes, after which it was dehydrated by pressure filtration. This washing and dehydration process was repeated three times, and the dehydrated product was dried in a hot air flow dryer at 105℃, and the dried product was crushed in a jet mill to obtain particles with good flowability.

[0141] Observation of the obtained particles under an electron microscope confirmed that the entire surface of the elastomer spherical particles was coated with spherical silica, and that silica-coated elastomer spherical particles (elastomer composite particles) were obtained. The aspect ratio of the silica-coated elastomer spherical particles (elastomer composite particles) obtained in Example 1 was 1.0.

[0142] The obtained silica-coated elastomer spherical particles (elastomer composite particles) were dispersed in water using a surfactant (polyoxyethylene lauryl ether), and measurements were performed using an electrical resistance particle size distribution measuring device (Multisizer 3, Beckman Coulter, Inc.). The particle size distribution was found to be equivalent to that of the aqueous dispersion of the above-mentioned elastomer spherical particles, and the volume average particle size was found to be approximately 5 μm.

[0143] [Production of Elastomer Composite Particles - Example 2] Elastomer composite particles were produced in the same manner as in Example 1, except that the elastomer spherical particles of Production Example 2 were used instead of the elastomer spherical particles of Production Example 1. As a result, silica-coated elastomer spherical particles (elastomer composite particles) with a volume average particle size of about 2 μm, in which spherical silica was attached and coated over the entire particle surface of the elastomer spherical particles, were obtained.

[0144] [Production of Elastomer Composite Particles - Example 3] Elastomer composite particles were produced in the same manner as in Example 1, except that the elastomer spherical particles of Production Example 3 were used instead of the elastomer spherical particles of Production Example 1. As a result, silica-coated elastomer spherical particles (elastomer composite particles) with a volume average particle size of about 11 μm, in which spherical silica was attached and coated over the entire particle surface of the elastomer spherical particles, were obtained.

[0145] [Production of Elastomer Composite Particles - Example 4] Elastomer composite particles were produced in the same manner as in Example 1, except that the elastomer spherical particles of Production Example 4 were used instead of the elastomer spherical particles of Production Example 1. As a result, silica-coated elastomer spherical particles (elastomer composite particles) with a volume average particle size of about 20 μm, in which spherical silica was attached and coated over the entire particle surface of the elastomer spherical particles, were obtained.

[0146] [Production of Elastomer Composite Particles - Example 5] In a 500 ml glass flask equipped with a paddle-type stirring blade stirrer, 100 g of the dispersion of elastomer spherical particles with a solid content of 20% obtained in Production Example 3, 184.9 g of pure water, and 0.2 g of a 30% aqueous solution of lauryl trimethyl ammonium chloride were charged. After adjusting the temperature of the aqueous dispersion to 5 to 10°C, 0.84 g of 5.0% ammonia water was added, and while maintaining the aqueous dispersion at 5 to 10°C, 12.5 g of methyltrimethoxysilane (an amount that would result in 22.0 parts of silane after hydrolysis and polycondensation reaction per 100 parts of elastomer spherical particles) was dropped over 15 to 20 minutes, during which the liquid temperature was maintained at 5 to 10°C and stirring was performed for 1 hour. The subsequent operations were the same as in Example 1, and fluid particles were obtained.

[0147] Observation of the obtained particles under an electron microscope confirmed that the entire surface of the elastomer spherical particles was coated with spherical polyorganosilsesquioxane, and that resin (polyorganosilsesquioxane)-coated elastomer spherical particles (elastomer composite particles) were obtained. In addition, the aspect ratio of the resin (polyorganosilsesquioxane)-coated elastomer spherical particles (elastomer composite particles) obtained in Example 5 was 1.0.

[0148] The obtained resin (polyorganosilsesquioxane)-coated elastomer spherical particles (elastomer composite particles) were dispersed in water using a surfactant (polyoxyethylene lauryl ether), and measurements were performed using an electrical resistance particle size distribution analyzer (Multisizer 3, Beckman Coulter, Inc.). The particle size distribution was found to be equivalent to that of the aqueous dispersion of the above-mentioned elastomer spherical particles, and the volume average particle size was found to be approximately 11 μm.

[0149] [Preparation of Elastomer Composite Particles - Example 6] Except for changing the amount of tetramethoxysilane added from 11.2 g (an amount that results in 22.0 parts of silica after hydrolysis and polycondensation reaction per 100 parts of elastomer spherical particles) to 5.6 g (an amount that results in 11.0 parts of silica after hydrolysis and polycondensation reaction per 100 parts of elastomer spherical particles), elastomer composite particles were produced in the same manner as in Example 1. As a result, silica-coated elastomer spherical particles (elastomer composite particles) with a volume average particle size of about 5 μm, in which spherical silica was attached and coated over the entire particle surface of the elastomer spherical particles, were obtained.

[0150] The particle size of the spherical silica or resin (polyorganosilsesquioxane) attached to or coated on the surface of the elastomer spherical particles obtained in each Example was as shown in the table below. [Table 1]

[0151] [Biodegradability evaluation] In accordance with the above evaluation method, the biodegradability of acrylic-modified poly-ε-caprolactone / polyether copolymer 1 was measured for 60 days at an incubation temperature of 22±1°C. As a result, the biodegradability of acrylic-modified poly-ε-caprolactone / polyether copolymer 1 was 62% on average after 28 days and 73% on average after 60 days, satisfying the judgment standard of 60% biodegradability after 28 days, and was therefore determined to be a "readily biodegradable substance." Therefore, it is assumed that the elastomer spherical particles, which are crosslinked particles of acrylic-modified poly-ε-caprolactone / polyether copolymer 1, and the composite particles will eventually decompose without remaining in the environment as particles if they are discharged directly into the ocean after use via land waters, etc.

[0152] The biodegradability of acrylic-modified poly-ε-caprolactone / polyether copolymers 2 to 4 was measured at an incubation temperature of 22±1°C for 60 days. As a result, the biodegradability of acrylic-modified poly-ε-caprolactone / polyether copolymers 2 to 4 was 40% on average after 28 days and 65% on average after 60 days, satisfying the judgment standard of 60% biodegradability after 60 days, and therefore was determined to be an “essentially biodegradable substance.” Therefore, it is presumed that the elastomer spherical particles, which are crosslinked particles of the acrylic-modified poly-ε-caprolactone / polyether copolymers 2 to 4, and the composite particles will eventually decompose without remaining in the environment as particles if they are discharged directly into the ocean via land waters after use.

[0153] The biodegradability of the acrylic-modified poly-ε-caprolactone / silicone copolymer was evaluated at an incubation temperature of 22±1°C for 28 days. The biodegradability of the acrylic-modified poly-ε-caprolactone / silicone copolymer remained at an average of 26% after 28 days, and no increase in biodegradability was observed thereafter. Since it did not meet the criterion of 60% biodegradability after 28 days, it was determined to be "not readily biodegradable."

[0154] The elastomer composite particles (resin or silica-coated elastomer spherical particles) of the present invention are expected to be particularly useful in cosmetics and the like due to their characteristic structural composition. In addition, since the powder / particle skeleton contains a degradable polyester structure (especially poly-ε-caprolactone) and a polyether structure, it is expected to exhibit and impart high biodegradability.

Claims

1. The elastomer composite particles have a volume average particle size of 0.5 to 200 μm, and are crosslinked particles of a copolymer having a polyester structure and a polyether structure. The elastomer composite particles have polyorganosilsesquioxane or silica on the surface of the elastomer spherical particles.

2. 2. The elastomer composite particle according to claim 1, wherein the copolymer is a polyester-polyether copolymer having at least two radically polymerizable unsaturated groups in one molecule.

3. 3. The elastomer composite particle according to claim 2, wherein the copolymer is a polyester-polyether copolymer represented by the following general formula (1) or (2): 【Chemistry 1】 (In general formula (1), R 1 each independently represents a divalent hydrocarbon group having 1 to 10 carbon atoms; R 2 each independently represents a radically polymerizable functional group-containing organic group represented by the following general formula (3a), (3b), or (3c), each k independently represents a number that is 1≦k≦10, each l independently represents a number that is 1≦l≦1,000, each m independently represents a number that is 1≦m≦1,000, and each n independently represents a number that is 1≦n≦100. In general formula (2), R 3 each independently represents a divalent hydrocarbon group having 1 to 10 carbon atoms; R 4 each independently represents a radically polymerizable functional group-containing organic group represented by the following general formula (4a) or (4b), each p is independently a number of 1≦p≦10, each l is a number of 1≦l≦1,000, each m is a number of 1≦m≦1,000, and each q is independently a number of 1≦q≦100. 【Chemistry 2】 (In general formulas (3a), (3b), (3c), (4a) and (4b), R 5 each independently represents a divalent hydrocarbon group having 1 to 8 carbon atoms; R 6 each independently represents a hydrogen atom or a hydrocarbon group having 1 to 3 carbon atoms.

4. 3. The elastomer composite particle according to claim 2, wherein the copolymer is a polyester-polyether copolymer represented by the following general formula (5): 【Chemistry 3】 (In general formula (5), R 1 each independently represents a divalent hydrocarbon group having 1 to 10 carbon atoms; R 2 each independently represents a radically polymerizable functional group-containing organic group represented by the following general formula (3a), (3b) or (3c), l is a number that satisfies 1≦l≦1,000, m is a number that satisfies 1≦m≦1,000, and each r is independently a number that satisfies 1≦r≦100. 【Chemistry 4】 (In general formulas (3a), (3b) and (3c), R 5 each independently represents a divalent hydrocarbon group having 1 to 8 carbon atoms; R 6 each independently represents a hydrogen atom or a hydrocarbon group having 1 to 3 carbon atoms.

5. A method for producing elastomer spherical particles, comprising the following steps i) to iii): i) A step of preparing a suspension composition by stirring and suspending the following components (A), (B), (C), and (D): (A) A copolymer having a polymerizable group and having a polyester structure and a polyether structure (B) an aqueous phase component or an oil phase component in which the component (A) is insoluble or poorly soluble (C) Suspension (D) Polymerization initiator ii) A step of obtaining a dispersion of elastomer spherical particles by radically polymerizing the component (A) in the suspension composition obtained in the step i). iii) A step of obtaining elastomer spherical particles by washing and drying to remove the continuous phase (B) from the dispersion of elastomer spherical particles obtained in the step ii).

6. The method for producing elastomer composite particles according to any one of claims 1 to 4, comprising the following step iv): iv) A step of adding the following component (I) to a liquid phase containing the following components (E), (F), (G), and (H) and subjecting the component (I) to a hydrolysis / polymerization reaction. (E) Elastomer spherical particles produced by the method according to claim 5, which are crosslinked particles of a copolymer having a polyester structure and a polyether structure and have a volume average particle size of 0.5 to 200 μm. (F) Alkaline substances (G) One or more selected from cationic surfactants and cationic water-soluble polymer compounds (H) Water (I) Trialkoxysilane or Tetraalkoxysilane

Citation Information

Patent Citations

  • Thermosetting epoxy resin composition

    JP1983219218A

  • Packer for one tank type washing machine

    JP1988012489A

  • Makeup cosmetic

    JP1988297313A

  • Conductive silicone rubber composition and cured product

    JP1990102263A

  • VTR

    JP1992017162A